Study Of Flight Operations Safety Area (KKOP) At Yogyakarta International Airport – Kulonprogo - Adenan, Adenan (Institut Transportasi dan Logistik Trisakti, 2024)
Yogyakarta-Kulon Progo International Airport is a replacement airport for Adisutjipto-Yogyakarta Airport which can no longer be expanded due to land limitations. Where the airport has an aerodrome reference code 4E instrumnet precision category I this is reviewed from the ultimate runway which has a size of 3,600 metres x 45 metres. Basically to determine the main boundaries of the Flight Operation Safety Area (KKOP) by looking at the difference in terrain height for the method used is qualitative with descriptive analysis. The location of the measurement in the Flight Operation Safety Area (KKOP) of Yogyakarta International Airport, the secondary data carried out is to analyse and determine the height of the obstacle. In determining the boundaries of the flight operation safety area (KKOP) around Yogyakarta-Kulon Progo International Airport using coordinate points applied in geographic coordinates there are obstacles, namely: three (3) hotel buildings located in the area below the horizontal surface in. The need for control and guidance by the Ministry of Transportation in order to maintain flight safety for buildings and objects growing in the Flight Operation Safety Area (KKOP) of Yogyakarta-Kulon Progo International Airport to ensure flight safety so as not to endanger flight operations.